The levels of circulating cytokines and risk of neuromyelitis optica spectrum disorder: a Mendelian randomization study - Ma, Xue; Wang, Yao; Chen, Xin; Guo, Jun (Frontiers in Immunology, 2024)
Background Neuromyelitis optica spectrum disorder (NMOSD) is an inflammatory autoimmune disease affecting the central nervous system (CNS). NMOSD pathogenesis involves systemic inflammation. However, a causal relationship between circulating cytokine levels and NMOSD remains unclear. Methods Mendelian randomization (MR) approaches were used to investigate the potential association between genetically determined circulating 19 inflammatory cytokines and 12 chemokines levels and the risk of developing NMOSD. Results After Bonferroni correction, the risk of aquaporin 4-antibody (AQP4-ab)-positive NMOSD was suggested to be causally associated with the circulating levels of three cytokines, including interleukin (IL)-4 [odds ratio (OR): 11.01, 95% confidence interval (CI): 1.16–104.56, P = 0.037], IL-24 (OR: 161.37; 95% CI: 2.46–10569.21, P = 0.017), and C-C motif chemokine 19 (CCL19) (OR: 6.87, 95% CI: 1.78–26.93, P = 0.006). Conclusion These findings suggest that a genetic predisposition to higher levels of IL-4, IL-24, and CCL19 may exert a causal effect on the risk of AQP4-ab-positive NMOSD. Further studies are warranted to clarify how these cytokines affect the development of AQP4-ab-positive NMOSD.